Homicides in Peru between 2017 and 2024: Epidemiological characterization and associated sociodemographic factors: Homicidios en Perú entre 2017 y 2024: Caracterización epidemiológica y factores sociodemográficos asociados - Prudencio-León, Walter Enrique (2025)
Objectives: To describe the epidemiological and temporal characteristics of homicides in Peru between 2017 and 2024, and to explore associated sociodemographic factors. Materials and methods: A cross-sectional, time-series epidemiological study was conducted using secondary data from the National Computerized System of Deaths (SINADEF). Homicide rates were calculated by sex, age, and department. Logistic regression models were fitted to identify associated factors, comparing homicide deaths with all other causes of death. Results: During 2017–2024, 10,266 homicides were recorded, predominantly among men (86.3%) with a median age of 32 years. Most cases occurred in public places, and three departments (Lima, La Libertad, and Callao) accounted for almost 60% of the cases. Homicide rates among men showed an upward trend throughout the period. Multivariate analysis revealed that the odds of dying from homicide were significantly higher in individuals with lower levels of education (Secondary: OR = 1.7; 95% CI 1.5–1.9) and marital status (divorced: OR = 1.5; 95% CI 1.3–1.7), compared to their respective reference groups. The most significant finding was that the homicide occurred in a public space, increasing the probability of death by homicide by 11.5 times (95% CI 10.7–12.3). Conclusion: These findings reaffirm the predominant victimization of young men and the concentration of homicides in public spaces, which is consistent with regional trends. The evidence from this study is crucial for developing more effective and targeted violence prevention interventions that address social vulnerabilities and target the most affected groups and areas, to reduce the public health burden of homicide and foster a safer society.